Implementasi Pendidikan Kewarganegaraan dalam Menguatkan Identitas Matakuliah Bela Negara di Era Digital - Prasetyo, Danang; Muharam, Ricky Santoso; Subagio, Hani; Yulianto, Wahyu Wibowo Eko; Sudaryatie, Sudaryatie (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Civic education in higher education is designed to strengthen students' spirit of state defence through concrete actions that provide benefits to the nation and state. This research seeks to uncover whether the educational materials studied at the higher education level make a positive contribution to inspiring students to make efforts to defend the country. The research method used is a mixture of quantitative and qualitative, the numbers from the questionnaire will be presented quantitatively and the data analysis is presented qualitatively descriptive. The results showed that the lecture material was very influential because 47% ‘strongly inspired’ students to defend the country, then 46% of students rated ‘inspiring’, and 7% ‘moderately inspiring’. As for the answer option ‘less inspiring’, no students chose it. Evidence that the lecture material provides inspiration by compiling an unstructured independent assignment project citizen with a civic engagement approach that has a positive impact on humanity and the natural environment. The evidence is compiled as an individual / group assignment report which is presented in the form of a file in the form of photos / videos accompanied by descriptive explanations and links to uploading the results of activities on social media with the title of the state defence campaign.